Edible Bird’s Nest Extract Reduced Expression of Senescence Markers in Bone Marrow Mesenchymal Stem Cells - Lina Elfita; Ietje Wientarsih; Dondin Sajuthi; Indra Bachtiar; Huda Shalahudin Darusman (Fakultas Farmasi Universitas Andalas, 2021)
Edible bird’s nest (EBN) is often consumed as a health food due to its suggested health benefits, including anti-aging effects, however the mechanism is still unknown. This study investigated the effect of EBN extract using long term expansion bone marrow-derived mesenchymal stem cells (BMMSCs) as an aging model. Passage 5 (P5) and passage 8 (P8) BMMSCs were treated with EBN extract, and their proliferation, senescence-associated β-galactosidase (SA-β-Gal) activity, and expression of p16INK4a were analyzed. Treatment of BMMSCs with EBN extract decreased population doubling time (PDT) in P5 but not in P8 BMMSCs. In P5 BMMSCs, 200 ppm EBN extract increased BMMSCs proliferation, with PDT reduced by 27.6%. However, 200 ppm EBN extracts did not affect P8 BMMSCs proliferation, although it increased BMMSCs viability. Treatment of P5 and P8 BMMSCs with 200 ppm EBN extract decreased SA-β-Gal activity by 54.8% and 47.1% of the control, respectively (P<0.05). Levels of p16INK4a expression were 5.4-fold lower in P5 BMMSCs treated with 200 ppm EBN extract compared to control (P<0.05). Similarly, treatment of P8 BMMSCs with 200 ppm EBN extract reduced p16INK4a mRNA level by 7.9-fold compared to the control (P<0.05). In order to investigate the pathway of EBN extract inhibition, we further analyzed IL-6 and NF-κB1 expression. Treatment of P5 and P8 BMMSCs with 200 ppm EBN extract reduced IL-6 mRNA levels by 7.9-fold and 2.1-fold of control, respectively (P<0.05). We found that 200 ppm EBN extract reduced NF-κB1 mRNA level approximately 2.4-fold both in P5 and P8 BMMSCs (P<0.05). Thus, EBN extract reduces markers of senescence, indicated by decreased SA-β-Gal activity and p16INK4a mRNA level, and this correlated with reduced messenger RNA levels of the pro-inflammatory factor IL-6 and the transcription factor NF-κB1.